2019
DOI: 10.1073/pnas.1906253116
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of an activin class ternary receptor complex reveals a third paradigm for receptor specificity

Abstract: TGFβ family ligands, which include the TGFβs, BMPs, and activins, signal by forming a ternary complex with type I and type II receptors. For TGFβs and BMPs, structures of ternary complexes have revealed differences in receptor assembly. However, structural information for how activins assemble a ternary receptor complex is lacking. We report the structure of an activin class member, GDF11, in complex with the type II receptor ActRIIB and the type I receptor Alk5. The structure reveals that receptor positioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(136 citation statements)
references
References 58 publications
(97 reference statements)
11
125
0
Order By: Relevance
“…This observation supports a key role for D406 in binding ACVR1. Our model is further supported by the fact that there is a conserved hydrophobic residue (M79 in ACVR1) that rests in a hydrophobic pocket formed by the Activin A dimer, forming a ‘knob-in-hole’ motif, which is also present in the BMP2:BMPR1A ( Allendorph et al, 2006 ) and GDF11•TGFBR1 complexes (PDB:2GOO, 6MAC) ( Goebel et al, 2019 ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This observation supports a key role for D406 in binding ACVR1. Our model is further supported by the fact that there is a conserved hydrophobic residue (M79 in ACVR1) that rests in a hydrophobic pocket formed by the Activin A dimer, forming a ‘knob-in-hole’ motif, which is also present in the BMP2:BMPR1A ( Allendorph et al, 2006 ) and GDF11•TGFBR1 complexes (PDB:2GOO, 6MAC) ( Goebel et al, 2019 ).…”
Section: Resultsmentioning
confidence: 57%
“…Substitution of the region encompassed by the pre-helix and post-helix region (amino acids 355 to 391 of mature Activin A) with the corresponding region from BMP2, switched type I (but not type II) receptor utilization ( Korupolu et al, 2008 ), whereas swapping the pre-helix region of Activin A with that of MSTN switched the preference of Activin A from ACVR1B to TGFBR1 ( Cash et al, 2009 ). Moreover, the recently solved structure of GDF11 (an Activin family ligand) in complex with TGFBR1 and ACVR2B (PDB:6MAC), shows that the finger two region is particularly important for determining type I receptor specificity for the Activin class ( Goebel et al, 2019 ). Superimposition of Activin A into this ternary complex predicts that Activin A’s finger two tip loop (F2TL; amino acids 406–409) also participates in binding to type I receptors ( Figure 3—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, activin A is a weak activator of SMAD1/5, whereas the heterodimer activin AB is approximately as potent as activin B. Type I receptors have been shown to bind at the interface between the two protomers in the dimeric ligand [43,44]. Thus, our observations raise the possibility that only one of the ligand protomers is needed to activate ALK2 signaling.…”
Section: Discussionmentioning
confidence: 58%
“…Sequences both in the receptors and the ligand determine binding specificity and strength. Recent studies have suggested that the finger 2 tip loops in activin A and GDF11 are important for their type I receptor binding specificities [44,45]. Moreover, in some cell types, only mutated ALK2, such as the variant encoded by ACVR1 (R206H), has been shown to relay a signal to SMAD1/5 after activin binding [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Activins exert their biological activity by interacting with cell surface tetrameric complexes consisting of 2 type I receptors (usually ALK4 or ALK7) and 2 type II receptors (usually ACVR2A or ACVR2B) [6]. As currently understood, the mature activin dimers initially bind to type II receptors with high affinity, and this results in recruitment of type I receptors and phosphorylation by the constitutively active type II kinase which activates the serine/thr kinase on the type I receptor [10]. The activated receptor complex subsequently phosphorylates SMAD2/3 proteins that combine with SMAD4 and translocate to the nucleus where they activate down-stream target genes.…”
Section: Introductionmentioning
confidence: 99%